Urgensi Etika bagi Komunikasi Politik - Michael Carlos Kodoati (Media: Jurnal Filsafat dan Teologi, 2023)
The writing aims to observe the urgency of ethics for political communication. Through literature research on Brian McNair's thought, one crucial question is revealed, is the increasing role of mass communication in the political process "good" or "bad" for democracy? McNair shows that political interaction in the public sphere is dirty and not by democratic ideals. In the end, it was found that political communication is a philosophical problem, in this case, ethics. However, bringing up the term political communication ethics ultimately fell on an oxymoron understanding. Even so, for the sake of democracy, there needs to be an understanding that the ethics of political communication is necessary after considering the dangers of political communication without ethics.